Investigative Judges as a Legal Transplant: Finnish Nineteenth-Century Criminal Procedure in Comparative Perspective - Heikki Pihlajamäki (Revista Brasileira de Direito Processual Penal)
After spreading widely in both Europe and Latin America in the early nineteenth century, the institution of the investigative judge began to gradually lose significance during the second half of the nineteenth century. This was the case both in France and in Germany. The main reason for the loss of significance was the development of criminalistics, professional criminal police and prosecutorial services. The investigative function that, following the old inquisitorial tradition, had fallen on the investigative judge at the beginning of the century, was no longer suited to the role of a judge. Instead, it made more sense to entrust criminal investigation to specialized professionals. When Finnish experts on criminal procedure set out to modernize the criminal law of the country in the 1890s, the investigative magistrate no longer seemed an interesting idea, and it did not seem reasonable to invest scarce professional resources in an institution that was losing significance. Instead, the legal resources would be better allocated to a professional corps of public prosecutors.